Um processo de negociação para o estabelecimento de contratos eletrônicos - Silva, Gabriel Costa (2010)
Organizations around the world cooperate with each other providing and consuming services. The web service technology allows organizations to overcome geographical and technological barriers, thus interacting within interorganizational business processes. These processes are regulated by electronic contracts. However, the establishment of an electronic contract, demand organizations to negotiate web services, their properties and the quality of service attributes. Organizations involved in shared business processes have different interests and point of view. A negotiation process allows organizations to discuss their interests, requirements and make concessions to reach an acceptable agreement between the parties so that they can establish a contract. Although the literature is rich in works dealing with negotiation, there is still a gap in respect to negotiation processes that provide guidelines for the dynamic negotiation of electronic contracts that contain web services. Our negotiation process considers human interaction and the use of different protocols in the same negotiation process. In addition, the web-based prototype of a computer support tool that implements the activities of the negotiation process was developed to allow the negotiation process. A feasibility study was conducted to evaluate the proposed process. It showed that the negotiation process is feasible and relevant to the parties involved in the negotiation process. The contributions of this work include: (i) the definition of a negotiation process; (ii) reuse of artifacts generated throughout the negotiation process; (iii) coverage of critical elements in the negotiation of contracts, such as role, features of electronic services and model contracts; and (iv) exploration of models in different application scenarios.